Trust and trustworthiness under information asymmetry and ambiguity - Clot-Figueras, Irma; Hernan-Gonzalez, Roberto; Kujal, Praveen (Elsevier, 2016)
We introduce uncertainty and ambiguity in the standard investment game. In the uncertainty treatment, investors are informed that the return of the investment is drawn from a publicly known distribution function. In the ambiguity treatment, investors are not informed about the distribution function. We find that both trust and trustworthiness are robust to the introduction of these changes.